UPLC-DAD-QTOF/MS Analysis of Flavonoids from 12 Varieties of Korean Mulberry Fruit - O-Chul Kwon; Wan-Taek Ju; Hyun-Bok Kim; Gyoo-Byung Sung; Yong-Soon Kim (Journal of Food Quality)
Mulberry (Morus alba L.) has been used in East Asia (Korea, China, and Japan) as a medicine because of its various pharmacological effects including the excellent antioxidant properties of its fruit. This study analyzed extracts from 12 varieties of Korean mulberry fruit for flavonoids using ultrahigh-performance liquid chromatography coupled with diode array detection and quadrupole time-of-flight mass spectrometry (UPLC-DAD-QTOF/MS). Six quercetin derivatives were identified by mass spectrometry (MS) based on the [quercetin + H]+ ion (m/z 303), while four kaempferol derivatives were identified based on the [kaempferol + H]+ ion (m/z 287). Two new compounds (morkotin A and morkotin C, quercetin derivatives) were identified for the first time in mulberry fruit. The total flavonoid contents of the mulberry fruits ranged from 35.0 ± 2.3 mg/100 g DW in the Baek Ok Wang variety (white mulberry) to 119.9 ± 7.0 mg/100 g DW in the Dae Shim variety. This study has, for the first time, evaluated the flavonoid chromatographic profiles of 12 varieties of Korean mulberry fruits in a following quali-quantitative approach, which will contribute to improved utilization of these fruits as health foods.